The consistency of cement pastes and their rheological parameters - Marta Kasińska; Jan Kempiński; Robert Świerzko (Acta Scientiarum Polonorum. Formatio Circumiectus, 2016)
This paper presents the results of the analysis of slump test parameters and rheological properties of cement pastes prepared with use of cement CEM II/B-V 32.5R. Slump parameters were determined with use of a special marked plate, while the rheological parameters were determined with use of the rotational viscometer Viscotester VT 550, manufactured by Haake, with coaxial cylinders, equipped with the MV2 system. Cement pastes consisted of a mixture of cement and water. The mixture concentration, described with use of the water to cement ratio W/C, fell into the range 0.65–0.33. In this study the dependence of the slump parameters on the water to cement ratio w/c was determined. The pseudo-curves of flow of cement pastes, obtained as a result of viscometric tests, were then adjusted to actual curves of flow and approximated with use of the tri-parametric, generalised Herschel-Bulkley model. The dependence of the rheological parameters of the model τo, k, n, as a function of the water to cement ratio w/c was calculated. The existing correlation between rheological parameters and slump parameters was determined for the analysed cement pastes.